2017
DOI: 10.3233/isu-170827
|View full text |Cite
|
Sign up to set email alerts
|

The state of the science of health literacy measurement

Abstract: Abstract. Advancing health literacy (HL) research requires high-quality HL measures. This article provides an overview of the state of the science of HL measurement at the level of the individual: where the field started, currently is, and should be going. It is divided into eight key sections looking at (1) the history of HL measurement, (2) the relationship between HL definitions and measurement, (3) the HL conceptual domains most and least frequently measured, (4) the methods used to validate HL measures, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
113
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(116 citation statements)
references
References 43 publications
0
113
0
3
Order By: Relevance
“…In 2013, a pre-post longitudinal evaluation of the Chronic Disease Self-Management Program among middle-aged and older adults was conducted across 17 states in the United States. This study reported that the program led to a statistically significant improvement in health literacy, quantified in this study using a limited measure assessing participants' confidence filling out medical forms [11].…”
Section: Introductionmentioning
confidence: 94%
“…In 2013, a pre-post longitudinal evaluation of the Chronic Disease Self-Management Program among middle-aged and older adults was conducted across 17 states in the United States. This study reported that the program led to a statistically significant improvement in health literacy, quantified in this study using a limited measure assessing participants' confidence filling out medical forms [11].…”
Section: Introductionmentioning
confidence: 94%
“…Objective instruments for measuring health numeracy can induce a burden in respondents that results in them struggling to answer the items [15]. Schapira et al [13] therefore emphasized the importance of including items with an appropriate level of difficulty.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In contrast, an objective instrument assesses the ability to process numeric information by asking respondents to answer specific questions, such as about the time to take the next medication. A subjective instrument requires less cognitive effort in responding to questions, whereas an objective instrument assesses health numeracy more accurately [15]. The third issue is related to the lack of psychometric properties.…”
Section: Introductionmentioning
confidence: 99%
“…Health literacy is, since it is the most established concept, also the one which has resulted in the largest number of measures. One review [47] has counted more than 150 measures and concludes that still no "gold standard" has emerged. Most measures are primarily focused on measuring health literacy on an individual level.…”
Section: Operationalizations and Measuresmentioning
confidence: 99%
“…Other measures that cover similar aspects are the Japanese functional, interactive and critical health literacy scales, which have also been translated to a Swedish context [49,50]. The use of subjective versus objective measures has been discussed by Nguyen et al [47], where both have advantages and drawbacks: subjective measures are generally easier to carry out, with less cognitive effort compared to objective tests of individual capabilities; a limitation is the lack of information about whether the reported skills are related to actual skills.…”
Section: Operationalizations and Measuresmentioning
confidence: 99%